On limit theorem for density function and asymptotic expansion in multidimensional case - Lapinskas, R. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. Лапинскас. О локальной предельной теореме и асимптотических разложениях в многомерном случаеR. Lapinskas. Apie lokalinę ribinę teoremą ir asimptotinius dėstinius daugiamačiu atveju